2013
DOI: 10.1002/vnl.20320
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial performance and the cure and mechanical properties of peroxide‐cured silicone rubber compounds

Abstract: Nanosilver colloid, Ag‐based zeolite compound, and 2‐hydroxypropyl‐3‐piperazinylquinolinecarboxylic acid methacrylate (HPQCAM) were used as antimicrobial agents and/or mechanical property improvers in peroxide‐cured silicone rubber vulcanizates. The vulcanizates were prepared by using a two‐roll mill followed by a hydraulic press in order to vulcanize the rubber compounds, and their cure characteristics, mechanical properties, and antibacterial performance were assessed. The antimicrobial performance of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The antibacterial agents used include nanosilver colloids, silver‐substituted zeolite compound (SSZ), and 2‐hydroxypropyl‐3‐piperazinylquinolinecarboxylic acid methacrylate (HPQM). In terms of silicone rubber compound, work by Taptim and Sombatsompop clearly suggested that HPQM was the most effective antibacterial agent when comparing nanosilver colloids and SSZ agents due to its organic structure and chemical compatibility with the silicone. This statement contradicted the work of Kaali et al , which found that the addition of (Ag+)‐loaded zeolite to silicone rubber improved the antimicrobial performance of the silicone, a result which was caused by the formation of the OH bond due to moisture contact with the (Ag+)‐loaded zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial agents used include nanosilver colloids, silver‐substituted zeolite compound (SSZ), and 2‐hydroxypropyl‐3‐piperazinylquinolinecarboxylic acid methacrylate (HPQM). In terms of silicone rubber compound, work by Taptim and Sombatsompop clearly suggested that HPQM was the most effective antibacterial agent when comparing nanosilver colloids and SSZ agents due to its organic structure and chemical compatibility with the silicone. This statement contradicted the work of Kaali et al , which found that the addition of (Ag+)‐loaded zeolite to silicone rubber improved the antimicrobial performance of the silicone, a result which was caused by the formation of the OH bond due to moisture contact with the (Ag+)‐loaded zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…The viable cell counts of bacteria are the number of bacteria growth as a function of contact time. A decrease in viable cell count with contact time indicates the inhibition of the bacteria growth [16].…”
Section: Antimicrobial Performance Of the Rubber Vulcanizatesmentioning
confidence: 99%
“…Our previous study [16] on the curing and mechanical properties, and antibacterial properties of silicone rubber filled with a wider range of antibacterial agents including nano-silver colloids, silver subtitled zeolite (SSZ), and 2-hydroxypropyl-3-piperazinyl-quinoline carboxylic acid methacrylate (HPQM) indicated that HPQM was most recommended for enhanced antibacterial performance with worsened mechanical properties. Therefore, this work aimed to improve the mechanical properties of the HPQM containing silicone rubber compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocidal polymers have the ability to kill microorganisms by acting as a source of sterilizing ions or molecules [1][2][3][4][5][6]. The use of polymeric antimicrobial agents have the advantage that they are nonvolatile, chemically stable, find it difficult to permeate through the skin of man or animal, and may enhance the efficacy of some existing antimicrobial agents and minimize the environmental problems accompanying the residual toxicity of the agents in addition to prolonging their lifetime [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%